Regional citrate anticoagulation for replacement therapy in patients with liver failure: A systematic review and meta-analysis - Peng, Bo; Lu, Jiaqi; Guo, Hebing; Liu, Jingyuan; Li, Ang (Frontiers in Nutrition, 2023)
Background citrate refers to an anticoagulant agent commonly used in extracorporeal organ support. Its application is limited in patients with liver failure (LF) due to the increased risk of citrate accumulation induced by liver metabolic dysfunction. This systematic review aims to assess the efficacy and safety of regional citrate anticoagulation in extracorporeal circulation for patients with liver failure. Methods PubMed, Web of Science, Embase, and Cochrane Library were searched. Studies regarding extracorporeal organ support therapy for LF were included to assess the efficacy and safety of regional citrate anticoagulation. Methodological quality of included studies were assessed using the Methodological Index for Non-randomized Studies (MINORS). Meta-analysis was performed using R software (version 4.2.0). Results There were 19 eligible studies included, involving 1026 participants. Random-effect model showed an in-hospital mortality of 42.2% [95%CI (27.2, 57.9)] in LF patients receiving extracorporeal organ support. The during-treatment incidence of filter coagulation, citrate accumulation, and bleeding were 4.4% [95%CI (1.6-8.3)], 6.7% [95%CI (1.5-14.4)], and 5.0% [95%CI (1.9-9.3)], respectively. The TBIL, ALT, AST, Scr, BUN, and LA decreased, compared with those before the treatment, and the total calcium/ionized calcium ratio, PLT, APTT, serum pH, BB, and BE increased. Conclusion Regional citrate anticoagulation might be effective and safe in LF extracorporeal organ support. Closely monitoring and timely adjusting during the process could reduce the risk for complications. More prospective clinical trials of considerable quality are needed to further support our findings.